Determination of propineb and its metabolites propylenethiourea and propylenediamine in banana and soil using gas chromatography with flame photometric detection and LC–MS/MS analysis. Issue 3 (4th March 2018) - Song, Shiming; Wei, Jie; Chen, Zhaojie; Lei, Yuhao; Zhang, Yan; Deng, Cheng; Tan, Huihua; Li, Xuesheng
ABSTRACT: A sensitive and specific method for the determination of propineb and its metabolites, propylenethiourea (PTU) and propylenediamine (PDA), using gas chromatography with flame photometric detection (GC-FPD) and LC–MS/MS was developed and validated. Propineb and its metabolite residue dynamics in supervised field trials under Good Agricultural Practice (GAP) conditions in banana and soil were studied. Recovery of propineb (as CS2 ), PDA and PTU ranged from 75.3 to 115.4% with RSD ( n = 5) of 1.3–11.1%. The limit of quantification (LOQ) of CS2, PDA and PTU ranged from 0.005 to 0.01 mg kg −1, and the limit of detection (LOD) ranged from 0.0015 to 0.0033 mg kg −1 . Dissipation experiments showed that the half-life of propineb in banana and soil ranged from 4.4 to 13.3 days. PTU was found in banana with a half-life of 31.5–69.3 days, while levels of PDA were less than 0.01 mg kg −1 in banana and soil. It has been suggested that PTU is the major metabolite of propineb in banana. The method was demonstrated to be reliable and sensitive for the routine monitoring of propineb and its metabolites in banana and soil. It also serves as a reference for the detection and monitoring of dithiocarbamates (DTCs) residues and the evaluation of their metabolic pathway.